2012
DOI: 10.1038/aps.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of hydrogen gas attenuates ouabain-induced auditory neuropathy in gerbils

Abstract: Aim: Auditory neuropathy (AN) is a hearing disorder characterized by abnormal auditory nerve function with preservation of normal cochlear hair cells. This study was designed to investigate whether treatment with molecular hydrogen (H 2 ), which can remedy damage in various organs via reducing oxidative stress, inflammation and apoptosis, is beneficial to ouabain-induced AN in gerbils. Methods: AN model was made by local application of ouabain (1 mmol/L, 20 mL) to the round window membrane in male Mongolian ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The denervatory effect of ouabain was originally observed in the cochlea of Mongolian gerbils by Schmiedt and coworkers [ 8 , 9 ] and corroborated by other authors [ 14 16 ]. It was subsequently demonstrated to occur as well in the cochlea of other rodent species, such as mouse [ 17 22 ] and rat [ 23 – 25 ], mostly in a dose-dependent way.…”
Section: Introductionsupporting
confidence: 68%
“…The denervatory effect of ouabain was originally observed in the cochlea of Mongolian gerbils by Schmiedt and coworkers [ 8 , 9 ] and corroborated by other authors [ 14 16 ]. It was subsequently demonstrated to occur as well in the cochlea of other rodent species, such as mouse [ 17 22 ] and rat [ 23 – 25 ], mostly in a dose-dependent way.…”
Section: Introductionsupporting
confidence: 68%
“…Numerous clinical studies have demonstrated that H 2 or HS exhibit antioxidative (9,11,12,38), anti-apoptotic (10) and anti-inflammatory (14,15) effects in several disease models. The protective effects of H 2 or HS on zymosan-induced organ impairment (14), lipopolysaccharide (LPS)-associated lung injuries (39), LPS-associated sepsis (15,38,40) and ouabain-induced auditory neuropathy (41) have also been observed in vivo. The results of the present study indicated that HM significantly inhibited oxidative damage in the SCs by selectively suppressing the production of ONOOand OH -, formation of 8-OHdG and activation of PARP-1, leading to a reduction in SC apoptosis via the caspase-independent and caspase-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, accumulating evidence from animal studies indicated a protective effect of H 2 pretreatment on the progression of organ damage in various types of disease models , such as ischemia-induced injury and dysfunction of the brain [22,33,39,55,59,[62][63][64], heart [34,45,59,65], liver [30], retina [41], and kidney [59,60]; stress-induced hippocampus dysfunction [38]; cisplatinum nephropathy [37,44]; transplanted intestinal graft [31,47]; corneal alkali burn [51]; ouabain-induced auditory neuropathy [66]; lung injury by oxygen toxicity [43,46]; paraquat [52]; extensive burns [54]; chronic allograft nephropathy [48]; and radiation injuries in various organs [49,50,55,68,69]. In Parkinson's disease [36,40] and Alzheimer's disease models [42], H 2 ameliorates neurodegenerative changes in the brain.…”
Section: The Hydrogen Gas Molecule As a Biological Antioxidantmentioning
confidence: 99%
“…In previous studies, H 2 was administered by inhalation [22,30,31,34,37,45,46,56,[62][63][64]66] or dissolved in water [22, 32-44, 47-55, 57-61, 65, 67-69]. Irrespective of the administration route, H 2 pretreatment could suppress oxidation, inflammation, and apoptosis while enhancing antioxidant reactions in those models.…”
Section: The Hydrogen Gas Molecule As a Biological Antioxidantmentioning
confidence: 99%